Multimodal Treatment of Unilateral Temporomandibular Disorder (TMD)- Study of 120 Cases - Kabir, Mohammad Iqbal; Islam Rabby, Md Atiqul; Taufique Reshma, Samira; Rab, Md Abdur; Haider, Ismat Ara; Chowdhury, Golam Mohiuddin (Medicine Today, 2025)
Introduction: Temporomandibular disorder (TMD) comprises a variety of conditions affecting the anatomy and functional characteristics of the TM joint (TMJ). Its prevalence has been reported to be between 3.7% and 12%, and is three to five times more frequent in women. Conservative treatments for TMD include medication, physiotherapy, occlusal splints, self-management strategies, and interventions based on cognitive behavioral approaches. Materials and Methods: It was a prospective study done over a period of 6 months in the department of Dental Surgery of Bangladesh Navy Hospital, BNS Potenga, Chattagram. Total 120 patients were included in the study. The patients who met the inclusion criteria were assigned randomly to the treatment. And all the patient got 1 month, 4 months & 6 months of follow up individually. Our treatment has been given in three phase (phase I, Phase II & Phase III). Result: After first line treatment total 51 (42.5%) patients were cure and rest of the 69 (57.5%) had the persistence symptoms. Then rests of the patients were received treatment under phase II guideline. And after phase II 48 (40%) patient became symptom free. Rests 21 (17.5%) patient were enrolled for phase III treatment where they were treated with occlusal splint following arthrocentesis plus Methylprednisolone injection. Among them 15 (12.5%) patients were cured but 6 (5%) had persistence moderate symptoms. Total success after completion of the study was 114 (95%). Conclusion: Analgesic with muscle relaxant, alone with soft diet and jaw exercise is a good first line treatment option in primary temporomandibular disorder. But in progressive cases occlusal splint with soft diet and jaw exercise give significant improvement. Medicine Today 2025, Vol.37 (1): 37-43